Construction and testing of a hydrogen cracking cell - F Sahra Gard (Iranian Journal of Physics Research, 2011)
A UHV atomic hydrogen-cracking cell has been constructed to produce atomic hydrogen in order to perform in-situ cleaning of semiconductor samples. The cell was calibrated and tested with the objective of cleaning the III-V semiconductor samples such as GaAs. Mass spectroscopy studies during the atomic hydrogen cleaning of the GaAs samples revealed the chemical process of the hydrogen cleaning. X-ray Photoemission Spectroscopy (XPS) was also carried out on the samples at different stages of cleaning. Desorption of the native oxide from GaAs samples resulted in a smooth surface, which was confirmed by Reflection High Energy Electron Diffraction (RHEED).